Closure of the Global Overturning Circulation Through the Indian, Pacific, and Southern Oceans: Schematics and Transports - Lynne D. Talley (Oceanography, 2013)
The overturning pathways for the surface-ventilated North Atlantic Deep Water (NADW) and Antarctic Bottom Water (AABW) and the diffusively formed Indian Deep Water (IDW) and Pacific Deep Water (PDW) are intertwined. The global overturning circulation (GOC) includes both large wind-driven upwelling in the Southern Ocean and important internal diapycnal transformation in the deep Indian and Pacific Oceans. All three northern-source Deep Waters (NADW, IDW, PDW) move southward and upwell in the Southern Ocean. AABW is produced from the denser, salty NADW and a portion of the lighter, low oxygen IDW/PDW that upwells above and north of NADW. The remaining upwelled IDW/PDW stays near the surface, moving into the subtropical thermoclines, and ultimately sources about one-third of the NADW. Another third of the NADW comes from AABW upwelling in the Atlantic. The remaining third comes from AABW upwelling to the thermocline in the Indian-Pacific. Atlantic cooling associated with NADW formation (0.3 PW north of 32°S; 1 PW = 1015 W) and Southern Ocean cooling associated with AABW formation (0.4 PW south of 32°S) are balanced mostly by 0.6 PW of deep diffusive heating in the Indian and Pacific Oceans; only 0.1 PW is gained at the surface in the Southern Ocean. Thus, while an adiabatic model of NADW global overturning driven by winds in the Southern Ocean, with buoyancy added only at the surface in the Southern Ocean, is a useful dynamical idealization, the associated heat changes require full participation of the diffusive Indian and Pacific Oceans, with a basin-averaged diffusivity on the order of the Munk value of 10–4 m2 s–1.